Clarifying stress corrosion cracking behavior of biomedical Mg-Gd-Zn-Zr alloy - Qiangsheng Dong; Jiahao Jiang; Jinghuai Zhang; Zhi Hu; Xiaobo Zhang (Journal of Magnesium and Alloys)
Implants are inevitably subjected to stress corrosion, bringing serious challenges to the controlled degradation of biomedical Mg alloys. It is worth studying the stress corrosion cracking (SCC) behavior of Mg alloy and exploring Mg alloy with good SCC resistance for wide biomedical applications. In this work, the as-cast and as-extruded Mg-3Gd-1Zn-0.4Zr (GZ31K) alloys with uniform corrosion were used to investigate SCC behavior. The as-extruded GZ31K alloy exhibited better corrosion resistance and mechanical properties than the as-cast one mainly owing to grain refinement and uniformly distributed fine precipitates, and possessed superior SCC resistance. To clarify the SCC mechanism, the slow strain rate tests were assisted with applied constant potentials via an electrochemical workstation. Accelerated anodic dissolution at anodic polarization deteriorated SCC resistance due to the initiation of corrosion pits and micro-cracks. However, cathodic polarization had no obvious effects on SCC resistance, along with both retarded corrosion and accelerated hydrogen evolution. Stacking faults in GZ31K alloy were hydrogen capture containers to reduce the effect of hydrogen on SCC resistance during cathodic polarization. These findings provide new insights into the evaluation of SCC mechanism, and offer more opportunities to explore Mg alloys with good SCC resistance by regulating anodic dissolution.